Is the probability of prenatal diagnosis or termination of pregnancy different for fetuses with congenital anomalies conceived following assisted reproductive techniques? A population‐based evaluation of fetuses with congenital heart defects. (6th March 2015) - Tararbit, K; Lelong, N; Jouannic, J‐M; Goffinet, F; Khoshnood, B; the EPICARD Study Group
<x xml:space="preserve">Abstract</x> Objective To compare the probability of prenatal diagnosis (PND) and termination of pregnancy for fetal anomaly (TOPFA) between fetuses conceived by assisted reproductive techniques (ART) and spontaneously‐conceived fetuses with congenital heart defects (CHD). Design Population‐based observational study. Setting Paris and surrounding suburbs. Population Fetuses with CHD in the Paris registry of congenital malformations and cohort of children with CHD (Epicard). Methods Comparison of ART‐conceived and spontaneously conceived fetuses taking into account potential confounders (maternal characteristics, multiplicity and year of birth or TOPFA). Main outcome measures Probability and gestational age at PND and TOPFA for ART‐conceived versus spontaneously conceived fetuses. Results The probability of PND (28.1% versus 34.6%, P = 0.077) and TOPFA (36.2% versus 39.2%, P = 0.677) were not statistically different between ART‐conceived (n = 171) and spontaneously conceived (n = 4620) fetuses. Estimates were similar after adjustment for potential confounders. Gestational age at PND tended to be earlier for ART fetuses (23.1 versus 24.8 weeks, P = 0.05) but no statistical difference was found after adjustment for confounders. Gestational age at TOPFA was comparable between ART‐conceived and spontaneously conceived fetuses. Conclusions In our population, ART conception was not significantly associated with the probability of PND or TOPFA for CHD. One implication of our results is that live births may be adequate for assessing the overall risk of CHD related to ART. However, total prevalence, in particular of severe CHD, would not be adequately assessed if TOPFA are not included.